Analysis of Determinants of Risk Factors for Hepatitis B Incidence in Pregnant Women in Makassar City - Kartini; Muharti Syamsul (Institute of Computer Science (IOCS), 2022)
Hepatitis B (HBV) infection in pregnant women has become a global concern because the most common transmission occurs worldwide, especially in endemic areas, namely mother-to-child transmission during the prepartum or perinatal period with the risk of contracting hepatitis B (HBV) infection. in children more than 90%. Quantitative research using observational analytic methods and case control study design was used to find risk factors. The sample size was obtained by means of